KONTRIBUSI PEMIKIRAN ASWAJA TERHADAP REGULASI HUKUM EKONOMI SYARI’AH DI INDONESIA - Pranoto, Singgih; Asaddullah , M. Aly; Bahrul Ulum, Median; Fitria, Norma (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Abstract : The contribution of Ahlussunnah wal Jamaah (Aswaja) thoughts to the formation and development of sharia economic law regulations in Indonesia. As one of the main streams of Islamic thought in Indonesia, Aswaja has a significant influence in integrating the values of fiqh muamalah, social ethics, and principles of justice in sharia economic law regulations. This research uses a qualitative approach with a literature study method, analyzing primary and secondary sources related to Aswaja thought and sharia economic law regulations in Indonesia. The results of this study indicate that Aswaja thought plays a role in providing normative, ethical, and practical foundations for the drafting of sharia economic law regulations, including in the aspects of sharia banking, financial institutions, and Islamic economic policies. Furthermore, Aswaja's moderate and contextual approach helps to align the principles of sharia with the needs of Indonesia's diverse society. Thus, Aswaja's thinking not only serves as a theological reference but also as a source of social and legal legitimacy in the development of sharia economic law regulations in Indonesia. Keywords: Aswaja, Islamic Thought, Sharia Economic Law,Regulation Indonesia